Creatine Transporter Deficiency: Screening of Males with Neurodevelopmental Disorders and Neurocognitive Characterization of a Case. Issue 4 (May 2016) - Thurm, Audrey; Himelstein, Daniel; D'Souza, Precilla; Rennert, Owen; Jiang, Susanqi; Olatunji, Damilola; Longo, Nicola; Pasquali, Marzia; Swedo, Susan; Salomons, Gajja S.; Carrillo, Nuria
ABSTRACT: Objective: Creatine transporter deficiency (CTD) is an X-linked, neurometabolic disorder associated with intellectual disability that is characterized by brain creatine (Cr) deficiency and caused by mutations in SLC6A8, the Cr transporter 1 protein gene. CTD is identified by elevated urine creatine/creatinine (Cr/Crn) ratio or reduced Cr peak on brain magnetic resonance spectroscopy; the diagnosis is confirmed by decreased Cr uptake in cultured fibroblasts, and/or identification of a mutation in the SLC6A8 gene. Prevalence studies suggest this disorder may be underdiagnosed. We sought to identify cases from a well-characterized cohort of children diagnosed with neurodevelopmental disorders. Method: Urine screening for CTD was performed on a cohort of 46 males with autism spectrum disorder (ASD) and 9 males with a history of non-ASD developmental delay (DD) classified with intellectual disability. Results: We identified 1 patient with CTD in the cohort based on abnormal urine Cr/Crn, and confirmed the diagnosis by the identification of a novel frameshift mutation in the SLC6A8 gene. This patient presented without ASD but with intellectual disability, and was characterized by a nonspecific phenotype of early language delay and DD that persisted into moderate-to-severe intellectual disability, consistent with previous descriptions of CTD. Conclusion: Identification of patients with CTD is possible by measuring urine Cr and Crn levels and the current case adds to the growing literature of neurocognitive deficits associated with the disorder that affect cognition, language and behavior in childhood.